Influence of Atmospheric Conditions on Labor Onset: A Single-Center Retrospective Cross-Sectional Study in Japan - Satoshi Hosoya; Tetsuro Tsujimoto; Hajime Oishi; Miyuki Sadatsuki (IMR Press, 2022)
Background: Although the mechanism underlying labor onset is controversial, there is an empirical finding that bad weather influences it. Previous reports have focused mainly on the relationship between the timing of deliveries and the weather conditions; fewer reports have focused on the timing of labor onset. Thus, we investigated the relationship for identifying atmospheric factors contributing to labor onset. Methods: We conducted a Japanese single-center retrospective cross-sectional study for identifying atmospheric factors contributing to labor onset over 8 years. We gathered daily atmospheric data in Tokyo from the official homepage of the Japan Meteorological Agency; mean barometric pressure, total solar irradiation, mean vapor pressure, and difference between the warmest and coldest temperatures. The percentage of days on which 1 or more laboring woman was hospitalized and the number of laboring women hospitalized per day were evaluated between low and middle/high groups for each atmospheric condition. Results: In total 1178 eligible women, the percentage of days significantly increased on days of low total solar irradiation (low group: 38% vs middle/high group: 31%; p < 0.001). The number of laboring women also significantly increased in such conditions (low group: 0.46 vs middle/high group: 0.38; p < 0.001). There were no significant differences in others. Conclusions: On days of low sunshine, pregnant women are more likely to start laboring. Further investigations will be needed to clarify the relationship between solar irradiation and labor onset.